Cu,Zn-ZSM-5 catalysts for CO2 hydrogenation by reverse water gas shift (RWGS) - Fonseca Couto, Lucas; Teixeira Cruz, Fernanda; Brandão dos Santos, Mauricio; Alves Fiuza-Junior, Raildo; Valverde Pontes, Karen; José Santos Mascarenhas, Artur (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Replacing fossil fuels with clean energy is essential to achieve the energy transition to low-carbon technology. One way to use CO2 is to convert it into platform molecules (building blocks) or sustainable fuels. Hydrogenation by reverse shift reaction (RWGS) activates CO2 into CO, which can be used as intermediate in the preparation of new products of interest, such as methanol, dimethyl ether (DME), among others. Cu/ZnO-Al2O3 catalysts are commonly studied for reverse shift reaction (RWGS) and have been shown to be quite active for this reaction, however, its CO2 conversion can still be improved, since its conversion obtained values of 56,1% under the conditions studied. In this work, Cu,Zn-ZSM-5 catalysts were prepared by the ion exchange method (simultaneously or successively), introducing Cu and/or Zn contents of 1.5%. The materials were characterized and tested in the RWGS reaction with a catalyst mass of 0.2 g, total gas flow rate of 50 mL min-1 and a H2:CO2:Ar ratio of 6:1:3 (F/W = 15000 mL g-1 h-1). The active phase for the reaction is the finely dispersed metallic Cu in the zeolitic support. The Cu-ZSM-5 catalyst reached 45,5% conversion with 100% selectivity to CO at 800°C, while showing low conversions at 400°C. The catalyst containing only Zn did not show significant activity, only at 800°C, reaching CO2 conversions of 35,5% and selectivity of 98% to CO. The material prepared by successive ion exchange, when Zn was added first than Cu, presented higher CO2 conversion, reaching 81% CO2 conversion and 99.9% CO selectivity at 800°C. On the other hand, when Cu was exchanged prior to Zn, conversions of 40,3% and 99.6% CO selectivity were observed. The material obtained by simultaneous exchange presented 31,9% conversion with 99.7% CO selectivity at 800°C. This shows that the order of exchange of Cu2+ and Zn2+ ions significantly influences the catalyst activity in the RWGS reaction. These materials were also compared with the Cu/ZnO-Al2O3 catalyst, which presents higher CO2 conversions in the temperature range of 300 to 600°C, but at higher temperatures no significant increase in conversion is observed, reaching a maximum conversion of 56,1% at 800°C with 99,9% of selectivity. The best performing Cu,Zn-ZSM-5 catalyst achieved better CO2 conversion results and very close selectivity when compared to Cu,Zn-Al2O3.At low temperatures, generally below 500°C, the formation of CH4 and, eventually, methanol is observed, which decreases with increasing temperature, favoring greater selectivity to CO from 500°C. The Cu,Zn-ZSM-5 catalysts presented a satisfactory catalytic performance under the conditions investigated, achieving high CO2 conversions and high selectivity to CO at higher temperatures. The introduction of Zn2+ ions prior to the Cu2+ ions causes a significant increase in the catalytic activity, emphasizing its role as a promoter. The RWGS can be a preliminary reaction in methanol synthesis, The RWGS may be a preliminary reaction in the synthesis of methanol, as the formation of methanol was observed at low temperatures, this fact will be investigated in the future.